Coaching Using Racial Literacy in Preservice Teacher Education. (December 2021) - Wetzel, Melissa Mosley; Daly, Annie; LeeKeenan, Kira; Svrcek, Natalie Sue
Drawing on a theoretical framework that centers race, racism, and anti-racism, this study explores a coaching conference in preservice literacy teacher education. In classrooms, teachers often encounter disruptions in the community; however, those disruptions are often seen as problems to be solved and are addressed without interrogating race discourses. This study builds on previous research that has explored how teachers engage in developing understandings about race in relation to their practice using discursive tools of racial literacy. We ask, How do three White teachers draw on race discourses that are racist and anti-racist within the context of one coaching event, a post-conference? Using critical discourse analysis, we describe and interpret how race discourses were drawn upon and disrupted in the conference. We conclude with a discussion of the racial literacy practices that have promise in this coaching context and in other professional settings.